Immunohistochemical Expression of FOXP3+ Regulatory T Cells in Proteinuric Primary Glomerulopathies - Vlachopanos, Georgios (Int J Nephrol, 2021)
FOXP3+ regulatory T-cell (Tregs) detection in renal allograft biopsies has been associated with a less intense immune response. Data about FOXP3+ Tregs' presence and role in primary glomerulopathies of native kidneys are minimal. We comparatively studied the immunohistochemical expression of FOXP3+ Tregs, CD4+ and CD3+ T cells in IgA nephropathy (IgAN), focal segmental glomerulosclerosis (FSGS), and membranous glomerulopathy (MGN). We retrospectively reviewed 71 renal biopsies (28 from patients with IgAN, 22 from patients with FSGS and 21 from patients with MGN) performed with proteinuria as the main indication. FOXP3+ Tregs and CD4+ and CD3+ T cells in inflammatory cell infiltrates of the interstitial tissue and periglomerular space were automatically counted using image analysis software. Univariable and multivariable logistic regressions were applied for statistical analysis. Nuclear FOXP3+ immunohistochemical expression was observed in T cells in 64% of IgAN cases, 77% of FSGS cases, and 76% of MGN cases (p > 0.05). Absolute FOXP3+ Tregs count in the interstitial tissue was higher in patients without arteriolar hyalinosis than in those with arteriolar hyalinosis (1.814 ± 2.160 vs. 831 ± 696; p = 0.029). In patients with a high FOXP3+/CD4+ ratio in the interstitial tissue, the odds ratio for CKD-EPI eGFR ≥60 ml/min/1.73 m(2) at biopsy was 4.80 (95% CI: 1.29–17.91; p = 0.019). FOXP3+ Tregs intrarenal infiltration in primary glomerulopathies is common. FOXP3+ Tregs' increased expression may be associated with milder histological lesions. High FOXP3+/CD4+ ratio in the interstitial tissue may have prognostic significance for renal function preservation.